PERAN DAN PROSPEK PESANTREN DALAM INDONESIA MODERN - Rizka Widayanti (STAI Darul Quran Payakumbuh, 2017)
Pesantren is a traditional educational institution in which students live and study together under the teachers’ guide, called Kiai, and have dormitory. It is a respective institution, especially Muslim society. At the same time, however, pesantren is not rare considered as an institution that blocks Islam's progress. This article discusses the role and prospect of pesantren. Starting from the beginning of its birth, in traditional society to model of pesantren the advancement of information technology. Pesantren has flourished long before the formal educational institution established in Indonesia. Thus, it has a great contribution to the development trend of modern society is certainly not easy for pesantren. Inside, it is an institution for the strengthening of religious and moral issues but on the other hand, it must be able to adapt in accordance with the development of modern society. For these challenges, pesantren can revitalize its role and prospect as educational institutions and community empowerment center.